A feasible visual investigation for associative foam >⧹ polymer injectivity performances in the oil recovery enhancement. (August 2018) - Davarpanah, Afshin
Graphical abstract: Highlights: Associative Foam \ Polymer injectivity with the polymer concentration of 1200 ppm is the best enhanced oil recovery scenario. Foam flooding in the absence of polymer particles has applied higher pressure drop. There is an appropriate agreement with the experimental investigation and simulation analysis. The increase of HPAM concentration lead to surface tension increase. The higher temperature had caused to the higher foam stability. Abstract: In the coming decades, regarding the enormous demands of fossil fuels in numerous industries, petroleum engineers try to find novel solutions to produced more oil volume and subsequently the most efficient techniques are applied to reach the sufficient hydrocarbon. Moreover, due to the low gas viscosity and gas density, the phenomenon of fingering and gravity segregation has occurred as a result of oil degradation. Foam Flooding is considered as one of the chemical methods to improve the oil recovery factor; in respect of the way, the utilization of foam increases the gas viscosity and thus improves the efficiency of the produced oil. The objective of this extensive study is to validate the model by the comparison of simulation analysis and experimental investigation for the studied field for the four different hydrolyzed polyacrylamide (henceforth; HPAM) concentration in the foaming injectivity scenarios and foam injectivity free of hydrolyzed polyacrylamide concentration scenario to achieve the best appropriate recovery factor scenario. Consequently, it is to be elaborated that experimental and simulation results are in a good agreement and HPAM with the concentration of 1200 ppm in the foaming agent has witnessed the maximum recovery factor. Furthermore, foam stability is utterly depended to the polymer concentration, and the effect of temperature would be a critical parameter to obtain the foam stability and viscosity measurement.